Serum Uric Acid and the Progression of Carotid Atherosclerosis: Association in a 10-year Chinese Cohort Study of a Health Check-up Population with Normal Uric Acid Levels - Lin LI, Yongsheng GU, Lu QIN, Weiliang HE, Hongzhen FAN, Kaihua ZHANG, Yingru SUN, Wannian ZHAO, Xiaoli NIU, Ci WEI, Litao LI, Hebo WANG (Zhongguo quanke yixue, 2022)
Background It is considered that serum uric acid (SUA), which may induce oxidative stress and vascular endothelial dysfunction, has a potential association with atherosclerosis, but it has not been fully clarified. Objective To investigate the association of high normal SUA level with the progression of carotid atherosclerosis. Methods A retrospective cohort design was used. Participants (n=7 074) were individuals who received two or more times of health examinations in Physical Examination Center, Hebei General Hospital from 2010 to 2019. All of them had no carotid atherosclerosis with normal SUA levels〔classified into quartiles of SUA: quartile 1 (n=1 794), quartile 2 (n=1 752), quartile 3 (n=1 785) and quartile 4 (n=1 743) 〕 at the enrolment. General information, physical examination, laboratory test indicators and carotid ultrasound indicators were collected. A follow-up was conducted with them until December 2019 with the prevalence of progression of carotid atherosclerosis〔defined as carotid intima-media thickness (cIMT) greater than 1 mm or carotid atherosclerosis prevalence detected by carotid ultrasound〕 as the endpoint. Cox regression analysis was used to explore the association of SUA with carotid atherosclerosis. Results Among the participants, 1 476 (20.86%) showed progression of carotid atherosclerosis. The prevalence of carotid atherosclerosis progression in quartiles 1-4 was 17.50% (314/1 794), 21.12% (370/1 752), 21.79% (389/1 785) and 23.12% (403/1 743), respectively, demonstrating a trend of growth with the increase in SUA level (χ2trend=3.58, P<0.001). After adjusting for confounding factors, Cox regression analysis showed that the risk of carotid atherosclerosis progression in quartile 4 group was higher than that in quartile 1 group〔HR=1.46, 95%CI (1.06, 2.01), P<0.05〕. Further analysis revealed that the risk of carotid atherosclerosis progression was higher in those aged less than 60 years〔HR=1.68, 95%CI (1.15, 2.45), P<0.05〕, men〔HR=1.52, 95%CI (1.04, 2.22), P<0.05〕, non-smokers〔HR=2.12, 95%CI (1.21, 3.71), P<0.05〕, non-drinkers〔HR=1.78, 95%CI (1.13, 2.79), P<0.05〕, those without metabolic syndrome〔HR=1.51, 95%CI (1.02, 2.23), P<0.05〕, and those with BMI≤24.0 kg/m2〔HR=1.75, 95%CI (1.09, 2.81), P<0.05〕 in quartile 4 group in comparison with the corresponding conventional counterparts in quartile 1 group. Conclusion The increase of SUA level within the normal range may be associated with increased risk of carotid atherosclerosis, and the risk may be higher in those aged <60 years, men, smoking history, no drinking history, no metabolic syndrome, or having BMI≤24.0 kg/m2.